KAJIAN PENINGKATAN PERANAN TRANSPORTASI MULTIMODA DALAM MEWUJUDKAN VISI LOGISTIK INDONESIA 2025 - Tulus Irpan H S; Imam Sony; Sarinah Sarinah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
In the last 10 years, the practice of logistics in the industry changing very remarkable. Global competition in the market of products and services to encourage the diversity of products to meet the needs of market segments are also diverse, high standard of product quality, timely delivery of goods is very dependent on the condition of public infrastructure provided by the government of a country. As a result, the demands of efficiency in higher logistics activities, including the level of security quality, safety and service. The lack of infrastructure support and the absence of "hub port" nationwide; poor management of interconnection or intermodal system between port infrastructure, transportation and warehousing as well as lower network capability, information technology led to the position of Indonesia is low in terms of competition and the logistics performance index compared with many countries in dunia.Tujuan research is to formulate the concept of multimodal transport role in realizing the Vision Logistics Indonesia 2025. The data was collected through a literature review, research results, and related scientific publications. The analysis uses qualitative descriptive approach, as well as to evaluate the public policy analysis to formulate the concept of multimodal transport role in realizing the vision of Indonesian Logistics 2025. The results are realizing the integration of the logistics system and increasing the role of multimodal transport, building a logistic center, to be able to realize the logistics system connectivity national.